PENGARUH PELATIHAN, KEPEMIMPINAN, DAN TRANSFORMASI DIGITAL TERHADAP KINERJA SEKTOR PUBLIK: MODEL REFORMASI SDM TERINTEGRASI - Didy Maharudin; Yuliana Yuliana; Sri Indra Yani (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study examines the integrated effects of human resource management reforms in Indonesia's public sector, focusing on the synergistic relationships between training effectiveness, transformational leadership, and digital transformation. Using a mixed-methods approach that combines quantitative surveys of 250 public sector employees with in-depth qualitative interviews of 15 senior administrators, this research provides compelling evidence that integrated HRM reforms produce significantly better outcomes than isolated interventions. The structural equation modeling analysis reveals that digital transformation serves as a powerful amplifier, enhancing training effectiveness by 45% and leadership impact by 38%. The study identifies three critical success factors for successful public sector HRM reform: strategic alignment with organizational objectives, technological infrastructure readiness, and comprehensive change management capabilities. These findings offer valuable insights for policymakers and public administrators seeking to enhance organizational performance through strategic human resource management. The research contributes to both theoretical understanding and practical implementation of public sector reforms in developing countries, particularly in the unique context of Indonesian bureaucracy. The integrated HRM reform model developed in this study explains 67% of variance in organizational performance, demonstrating its strong predictive power and practical utility for public sector transformation initiatives.